(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Fat-phobic cultural practices produce suffering apart from the socioverbal community that suffers punishment because of their body weight. Such punishments produce intense physiological changes and actions to avoid or eliminate the probability of contact with events that exert an aversive function. This article is an case report of a psychotherapeutic process , whose objective was to evaluate implications of fatphobic cultural practices in the production of inadequacy and incapacity behaviors. We performed 48 sessions. During the sessions, it was possible to notice the formulation of the self-rule “I am unable because I am fat” (sic.), relating performance, in different contexts, to body weight. Faced with situations of social interaction, the client presented physiological changes and behavioral repertoire of escape and avoidance. With the psychotherapeutic process, the client began to expose herself to new situations and, with that, access reinforcers and discriminate that the performance in her socioverbal interactions is not necessarily related to the size of her body.